2020
DOI: 10.1088/1755-1315/440/5/052081
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Analysis of the Axial Force of Pump-Turbine during Load-Rejection Process

Abstract: Load-rejection is an important process of pump-turbine unit. In this process, hydraulic characteristics would change greatly. The axial force of runner and of the entire shaft system will be impacted. This study focuses on a prototype pump-turbine unit. The axial force of this unit during load-rejection is predicted and analyzed. The hydraulic transient analysis can give a more accurate boundary condition of pumpturbine. The computational fluid dynamics simulation considering the full leakage in runner crown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, a transient process calculation took months even with many computational resources, which could not provide fast feedback to the PT designers of real engineering projects within a given time frame. For this reason, some scholars [26,27,[37][38][39] have proposed a simplified method to calculate the fluid flow at each critical moment of transient processes and to study the flow-induced stresses of PT structures. This calculation method requires substantially less time and computational resources, and the simulation results agree well with corresponding measured ones.…”
Section: Methodology Of Flow-induced Stress Analysismentioning
confidence: 99%
“…However, a transient process calculation took months even with many computational resources, which could not provide fast feedback to the PT designers of real engineering projects within a given time frame. For this reason, some scholars [26,27,[37][38][39] have proposed a simplified method to calculate the fluid flow at each critical moment of transient processes and to study the flow-induced stresses of PT structures. This calculation method requires substantially less time and computational resources, and the simulation results agree well with corresponding measured ones.…”
Section: Methodology Of Flow-induced Stress Analysismentioning
confidence: 99%
“…In recent years, the joint 1D/3D simulation method combining 1D pipeline calculation with 3D unsteady flow calculation of turbines [14][15][16][17] has been mostly used to study the transient processes of hydraulic turbine units. The 1D/3D joint simulation method can more accurately calculate key parameters such as rotational speed, flow rate and guide vane opening of the turbine unit and achieve valuable results for hydropower engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions of hydraulic axial thrust reduction of pumps were then presented [19,20]. In terms of the load-rejection of generating mode, the axial force variation was found to have a strong relationship with flow rate [21]. Li et al [22] found that the amplitude of the force depends on the operating conditions and the guide vane openings.…”
Section: Introductionmentioning
confidence: 99%